2022
DOI: 10.22270/jddt.v12i4.5538
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony stimulating factor (GCSF) protected in ovarian tissues against ischemia-reperfusion injury

Abstract: Ovarian torsion is an important reproductive gynecological emergency in daily life and physiology. Granulocyte colony stimulating factor (G-CSF) is a glycoprotein capable of hematopoietic development and successfully used in the treatment of congenital granulocytopenia. In our study, we aimed to investigate protective effects of G-CSF on ovarian ischemia reperfusion (IR) immunohistochemically. Four groups were used. In control group, abdomen was opened and closed with the surgical protocol. The rats in the G-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ovarian ischemia reperfusion causes many pathologies in ovarian tissues, as well as remote organs such fallopian tubes, uterine and cervix. Aktaş et al studied ovarian IR and found intense fibrosis, vascular dilatation and congestion, stromal inflammation in ovarian tissues after IR 12 . Peker et al investigated IR injury in ovarian tissues and revealed that IR caused edema, inflammation, congestion, degenerated follicles, and cells with pyknotic nuclei 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian ischemia reperfusion causes many pathologies in ovarian tissues, as well as remote organs such fallopian tubes, uterine and cervix. Aktaş et al studied ovarian IR and found intense fibrosis, vascular dilatation and congestion, stromal inflammation in ovarian tissues after IR 12 . Peker et al investigated IR injury in ovarian tissues and revealed that IR caused edema, inflammation, congestion, degenerated follicles, and cells with pyknotic nuclei 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The harmful effects of free oxygen radicals (ROS) formed as a result of ischemia increase with the reperfusion into the tissues during the reperfusion phase. 18 . The brain is one of the most important organs to be affected by ischemia reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Both ischemia and reperfusion can cause damage to tissues separately. The harmful effects of free oxygen radicals (ROS) formed as a result of ischemia are increased by reperfusion into the tissues 15 . Intestinal ischemia, whose mortality varies between 60-80%, is one of the most important abdominal emergencies 16 .…”
Section: Discussionmentioning
confidence: 99%